2021
DOI: 10.1177/20587392211002657
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Streptococcus suis by nanopore sequencing in endophthalmitis: A case report

Abstract: Endophthalmitis is a rare and infectious disease caused by Streptococcus suis (S suis). Traditionally, S suis is detected by the pathogenic microorganism culture method, which has low positivity and high false negativity. Nanopore sequencing (NS), which is a third-generation sequencing technology, has several advantages over the traditional method; in particular, it is cost and time effective and has a high throughput. In this report, a case of infectious endophthalmitis caused by trauma is examined. The NS re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Streptococcus suis is traditionally detected by the pathogenic microorganism culture method; however, this method is unreliable because of the high number of false negatives. Recently, a case report by Wang et al 6 presented detecting S. suis by nanopore sequencing in posttraumatic endophthalmitis, which has several advantages over the traditional method. Interestingly, our case report indicated that iris necrosis might be an important sign of ophthalmic complication due to S. suis .…”
Section: Discussionmentioning
confidence: 99%
“…Streptococcus suis is traditionally detected by the pathogenic microorganism culture method; however, this method is unreliable because of the high number of false negatives. Recently, a case report by Wang et al 6 presented detecting S. suis by nanopore sequencing in posttraumatic endophthalmitis, which has several advantages over the traditional method. Interestingly, our case report indicated that iris necrosis might be an important sign of ophthalmic complication due to S. suis .…”
Section: Discussionmentioning
confidence: 99%